2018
DOI: 10.1039/c7bm01186e
|View full text |Cite
|
Sign up to set email alerts
|

Engineering ellipsoidal cap-like hydrogel particles as building blocks or sacrificial templates for three-dimensional cell culture

Abstract: Hydrogel particles that can be engineered to compartmentally culture cells in a three-dimensional (3D) and high-throughput manner have attracted increasing interest in the biomedical area. However, the ability to generate hydrogel particles with specially designed structures and their potential biomedical applications need to be further explored. This work introduces a method for fabricating hydrogel particles in an ellipsoidal cap-like shape (i.e., ellipsoidal cap-like hydrogel particles) by employing an open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…We found that their droplet hanging ability reduces with the decrease of angles between the branch and center shaft as well (Figure 2h). Compared with the traditional open‐pore hanging droplet method, [ 41 ] our bioinspired microstructure platform offers a larger contact area and could hold droplets more firmly, and the preparation process of this rigid structure is convenient with scaling‐up potential.…”
Section: Resultsmentioning
confidence: 99%
“…We found that their droplet hanging ability reduces with the decrease of angles between the branch and center shaft as well (Figure 2h). Compared with the traditional open‐pore hanging droplet method, [ 41 ] our bioinspired microstructure platform offers a larger contact area and could hold droplets more firmly, and the preparation process of this rigid structure is convenient with scaling‐up potential.…”
Section: Resultsmentioning
confidence: 99%
“…MSCs have been well-known for their capacity to differentiate desired cell types based on the inducible growth factors. ,, In this study, MSC spheroids were induced to differentiate into chondrocytes using TGF-β3, which has been extensively used in chondrogenesis research in vitro . First, the morphologies of the induced MSC spheroids cultured inside the generated microwell at days 2, 14, and 30 were observed under a microscope (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…The sacrificial template approach has been wellknown as an effective microfabrication technology method to create cell-friendly scaffolds for tissue engineering owing to its biocompatibility and high-molding effectiveness. 30 Figure 5a illustrates a detailed procedure of microwell fabrication by sacrificing the tadpole-egg-shaped alginate fiber (A−C) and the culture of MSCs to form spheroids inside the microwells (D). To fabricate the microwell, the fiber template was first half-dipped into agarose solution and was melted at 50 °C.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…156 Furthermore, the inclusion of magnetic nanoparticles enabled cell-laden microgel manipulated by an external magnetic field. 155,156,223 Even though mentioned studies produce microgels with specific geometries, few or no comparisons have been made between geometries on aspects such as cell viability or proliferation. To this end, the effect of varying circularity of methacrylated chitosan hydrogels from spheres to spheroids on the viability of encapsulated L929 cells was studied.…”
Section: Tissue Engineeringmentioning
confidence: 99%